Associations between food insecurity and diabetes risk factors in US adolescents in the National Health and Nutrition Examination Survey (NHANES) 2007-2016 - Aarohee P Fulay; Joyce M Lee; Ana Baylin; Julia A Wolfson; Cindy W Leung (Cambridge University Press, 2024)
Abstract Objective: To evaluate the associations between household food insecurity and diabetes risk factors among lower-income US adolescents. Design: Cross-sectional analysis. Household food security status was measured using the 18-item Food Security Survey Module. Simple and multivariable linear and logistic regressions were used to assess the association between food security status and fasting plasma glucose (FPG), oral glucose tolerance test (OGTT), HbA1C and homoeostatic model assessment - insulin resistance (HOMA-IR). The analyses were adjusted for household and adolescent demographic and health characteristics. Setting: USA. Participants: 3412 US adolescents aged 12-19 years with household incomes ≤300 % of the federal poverty line from the National Health and Nutrition Examination Survey cycles 2007-2016. Results: The weighted prevalence of marginal food security was 15·4 % and of food insecurity was 32·9 %. After multivariate adjustment, adolescents with food insecurity had a 0·04 % higher HbA1C (95 % CI 0·00, 0·09, P-value = 0·04) than adolescents with food security. There was also a significant overall trend between severity of food insecurity and higher HbA1C (P trend = 0·045). There were no significant mean differences in adolescents' FPG, OGTT or HOMA-IR by household food security. Conclusions: Food insecurity was associated with slightly higher HbA1c in a 10-year sample of lower-income US adolescents aged 12-19 years; however, other associations with diabetes risk factors were not significant. Overall, this suggests slight evidence for an association between food insecurity and diabetes risk in US adolescents. Further investigation is warranted to examine this association over time.